Liver injury in chronic alcoholism: clinical, laboratorial and histological correlation. - Saragoça, A. (1981)
Liver cirrhosis is responsible for a large number of deaths in our country as well as in many other parts of the world. In Portugal, during the year 1975, cirrhosis was the second most common cause of death among individuals between the ages of 25 and 44 and the third between the ages of 45 and 64. The mortality rate due to this disease is higher in rural areas where the population is predominantly composed of peasants with a low standard of living and where wine production per capita is higher.